On the spectrum of a distribution function and on unique factorization - T. Pham-Gia (International Journal of Mathematics and Mathematical Sciences)
The spectrum of a distribution function is related to the quasi-analyticity of a class of functions {CM(j)}, where M(j) is a multisequence of positive numbers. For a regular multisequence, a result on the uniqueness of characteristic function decomposition is given.